The molecular genetics of dupuytren disease - Ng, M (2018)
Dupuytren disease (DD) is a fibromatosis of the fascia of the hand. It affects around 4% of the population in the UK. Treatment for DD is dominated by surgery, but the recurrence rate after surgery is high. There are also no existing treatments to prevent progression of early disease, and reduce the need for surgery. At the cellular level, the fibrotic environment in DD is similar to that of other tissue specific fibrotic condition of other organs, such as lung and liver where myofibroblasts and some immune cells are found residing in a rich extracellular matrix. Although myofibroblast cells are thought to be the driving force in the development of DD, no effective biomarkers have been identified to date. Many different cell types have been suggested to be the origin of the myofibroblast cell population, but often without any solid evidence. As a result, the aetiology of DD remains poorly understood. The advent of high through put sequencing and genotyping techniques provided me with a new approach to the investigation of the pathophysiology of DD. DD is a complex genetic disease, with a heritability of 80% - very similar to type I diabetes. Currently, the most effective method to interrogate a complex genetic disease is a GWAS. In the second chapter of my thesis, I report a total of 17 novel associated variants discovered with this approach. I prioritised variants for functional mechanistic studies through fine mapping and in silico analysis using epigenomic and transcriptomic public databases. Follow-up functional analysis on SFRP4 and DDR2, in chapters II and III respectively, assess transcriptomic expression and various fibrotic phenotypes such as cell migration in diseased myofibroblasts resected from patients with DD. These analyses have revealed the pro-fibrotic nature of these proteins, and suggest potential new therapeutic targets. In studying DDR2, I have also demonstrated that different collagen types can alter the myofibroblast cell function from pro-fibrotic to pro-inflammatory.